2018
DOI: 10.1042/bcj20180010
|View full text |Cite
|
Sign up to set email alerts
|

A novel rhodopsin phosphodiesterase from Salpingoeca rosetta shows light-enhanced substrate affinity

Abstract: It is since many years textbook knowledge that the concentration of the second messenger cGMP is regulated in animal rod and cone cells by type II rhodopsins via a G-protein signaling cascade. Microbial rhodopsins with enzymatic activity for regulation of cGMP concentration were only recently discovered: in 2014 light-activated guanylyl-cyclase opsins in fungi and in 2017 a novel rhodopsin phosphodiesterase (RhoPDE) in the protist (RhoPDE). The light regulation of RhoPDE, however, seemed very weak or absent. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
42
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(43 citation statements)
references
References 19 publications
1
42
0
Order By: Relevance
“…Although choanoflagellates are unpigmented and transparent, at least four choanoflagellates (9) encode a choanoflagellate-specific rhodopsin-phosphodiesterase fusion protein ( Fig. S2), RhoPDE, that has been investigated for its potential as an optogenetic tool (20)(21)(22)(23). RhoPDE proteins consist of an N-terminal type I (bacterial) rhodopsin (a class of photosensitive transmembrane proteins broadly involved in light detection (24)) fused to a Cterminal phosphodiesterase (PDE) that catalyzes light-dependent cyclic nucleotide hydrolysis (25), which act on the timescale of transcriptional regulation (at least several minutes (26,27)) and therefore appear unlikely to mediate the light-to-dark transition response.…”
Section: A Rhodopsin-cgmp Pathway Regulates Colony Inversion In Respomentioning
confidence: 99%
See 1 more Smart Citation
“…Although choanoflagellates are unpigmented and transparent, at least four choanoflagellates (9) encode a choanoflagellate-specific rhodopsin-phosphodiesterase fusion protein ( Fig. S2), RhoPDE, that has been investigated for its potential as an optogenetic tool (20)(21)(22)(23). RhoPDE proteins consist of an N-terminal type I (bacterial) rhodopsin (a class of photosensitive transmembrane proteins broadly involved in light detection (24)) fused to a Cterminal phosphodiesterase (PDE) that catalyzes light-dependent cyclic nucleotide hydrolysis (25), which act on the timescale of transcriptional regulation (at least several minutes (26,27)) and therefore appear unlikely to mediate the light-to-dark transition response.…”
Section: A Rhodopsin-cgmp Pathway Regulates Colony Inversion In Respomentioning
confidence: 99%
“…3A). Based on in vitro studies(20)(21)(22)(23), RhoPDE from S. rosetta appears capable of converting a photic stimulus into a biochemical signal within seconds, similar to the time scale of the C. flexa response to light-to-dark transitions. To test for the presence of RhoPDE or other candidate photosensitive proteins in C. flexa, we sequenced and assembled the C. flexa transcriptome (Figshare DOI 10.6084/m9.figshare.8216291).…”
mentioning
confidence: 97%
“…While animal rhodopsins are mainly photosensory receptors as a specialized subset of G-protein-coupled receptors (1)(2)(3)(4), microbial rhodopsins have various functions, including photosensory receptor, light switch for gene expression, photoactivated enzyme, light-driven ion pump and light-gated ion channel (1,(5)(6)(7)(8)(9)(10). Animal and microbial rhodopsins share a common architecture of seven transmembrane a-helices, though presence of an extra N-terminal transmembrane helix was reported for enzyme rhodopsins (11)(12)(13). Animal and microbial rhodopsins have no significant sequence similarity to warrant a derivation from a common ancestor.…”
Section: Introductionmentioning
confidence: 99%
“…A putative molecular mechanism to explain Rh-PDE activation was proposed based on a series of studies that examined the full-length protein. Two recent papers revealed that Rh-PDE possesses eight transmembrane helices, not seven, such that both the N and C terminus face the cytoplasmic side (16,17). In addition, the crystal structure of the PDE domain was determined (16), and a better construct than the WT for optogenetic application was reported (17).…”
mentioning
confidence: 99%
“…Two recent papers revealed that Rh-PDE possesses eight transmembrane helices, not seven, such that both the N and C terminus face the cytoplasmic side (16,17). In addition, the crystal structure of the PDE domain was determined (16), and a better construct than the WT for optogenetic application was reported (17). The light-induced mechanism of activation of Rh-PDE enzymatic activity is particularly intriguing, and to assess it, in vivo and in vitro studies have been extensively initiated.…”
mentioning
confidence: 99%